El control formal y sustancial de la acusación fiscal en la etapa intermedia del proceso penal y la garantía del debido proceso legal - Horna Guevara, Pedro Antonio (2010)
The present investigation deals with a novel and very controversial subject, the same one that is of great importance in our reality, the problematic revolves around "the formal and substantial control of the prosecution in the intermediate stage of the criminal process and the guarantee of due legal process". In the development of the present investigation we used methods and data collection techniques such as the dogmatic method, comparative method, method of analysis and synthesis among others. Also, the techniques used as observation and signing were appropriate for the development of the subject under study. In the first chapter all the general aspects of the criminal process are developed in the light of the doctrine and the national legislation; The second chapter refers to the preparatory investigation, the third chapter touches the intermediate stage, in the fourth chapter concerning the oral trial and finally in the fifth chapter regarding the case study. The results have been embodied in concept maps, which will allow us a more didactic explanation of the discussion of results. The conclusions and recommendations cover the objectives of the research developed in such a way as to be relevant and applicable to the existing reality in the field of criminal law